Acanthocytosis as a predisposing factor for non-ketotic hyperglycaemia induced chorea-ballism. Issue 12 (16th November 2005) - Pisani, A; Diomedi, M; Rum, A; Cianciulli, P; Floris, R; Orlacchio, A; Bernardi, G; Calabresi, P
Abstract : Background: Episodic non-ketotic hyperglycaemia in patients with diabetes may be responsible for a syndrome characterised by hemichorea-hemiballism associated with unique radiological features. Objective: To investigate whether factors other than hyperglycaemia may be responsible for the neurological involvement. Methods: Three patients who developed a persistent chorea-ballism syndrome triggered by a hyperglycaemic crisis were investigated. In these patients, the persistence of the involuntary movements required neuroleptic medication. Results: T1 weighted magnetic resonance imaging revealed bilateral hyperintense lesions involving the striatum. Surprisingly, in these patients, the laboratory investigations revealed peripheral red blood cell acanthocytosis in a significant proportion of cells. Conclusion: Compared with the large population of patients with diabetes who do not show abnormal involuntary movements, unrecognised acanthocytosis in diabetes might render patients prone to develop hemichorea-hemiballism.